Analysis of flow through screen in open channel [compact disc] - 213239 Amalludin Zolkifli (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Sarjana Muda Kejuruteraan Awam) - Universiti Teknologi Malaysia, 2003